Dissecting Long-Term Adjustments of Photoprotective and Photo-Oxidative Stress Acclimation Occurring in Dynamic Light Environments - Matsubara, Shizue; Schneider, Trang; Maurino, Veronica G. (Frontiers in Plant Science, 2016)
Changes in light intensity directly affect the performance of the photosynthetic apparatus. Light energy absorbed in excess of cells’ needs leads to production of reactive oxygen species and photo-oxidative damage. Excess light in both constant and dynamic environments induces photoprotective acclimation in plants. Distinct sets of signals and regulatory mechanisms are involved in acclimatory adjustment of photoprotection and photosynthesis under constant and dynamic (fluctuating) light conditions. We are still far away from drawing a comprehensive picture of acclimatory signal transduction pathways, particularly in dynamic environments. In this perspective article, we propose the use of Arabidopsis plants that produce H2O2 in chloroplasts (GO plants) under atmospheric CO2 levels as a tool to study the mechanisms of long-term acclimation to photo-oxidative stress. In our opinion there are new avenues to future investigations on acclimatory adjustments and signal transduction occurring in plants under dynamic light environments.